Dampak Model Pembelajaran Discovery Learning Terhadap Keterampilan Proses Sains Dan Hasil Belajar Kognitif Siswa Sekolah Dasar - Tamalene, Asri S.; Jusuf, Ridwan (EDUKASI, 2024)
Science learning in elementary schools is given to students to practice science process skills. Through science learning, students can produce a conceptual understanding of material through scientific work. This research aims to determine students' science process skills and cognitive learning outcomes through the Discovery Learning learning model in elementary schools. This research method is experimental research with a Posttest-Only Control Design. The results showed that the cognitive learning outcomes and skills of experimental class students were higher than those of control class students. Based on the results of the first hypothesis test, it was found that Fcount= 131.266 while Ftable= 3.44. This means FcountFtable and sig. = 0.05 so H0 is rejected and Ha is accepted. So it can be concluded that there are differences in cognitive learning outcomes between students who take part in learning using the discovery learning model and students who take part in conventional learning. The results of the second hypothesis test showed that the value of Fcount = 128.380 while Ftable = 3.44. This means FcountFtable and sig. = 0.05 so H0 is rejected and Ha is accepted. So it can be concluded that there are differences in science process skills between students who take part in learning using the discovery learning model and students who take part in conventional learning.